Geoinformation support for the management of lands of the nature reserve fund within the Kyiv region - Koshel, A.; Kolhanova, I. (Land Management, Cadastre and Land Monitoring, 2023)
The nature reserve fund and other protected areas that have this status are of great importance for the purposes of rational use and protection of land resources. In this context, the main purpose of the study presented in this article was the formation of scientific approaches to the effective management of the lands of the nature reserve fund based on the use of modern geographic information support. It is emphasized that the area of lands of the nature reserve fund and other nature protection purposes has a low percentage and requires bringing their share to at least 15%. An important problem is the lack of projected boundaries of the lands of the nature reserve fund for most of these objects with their subsequent inclusion in the National cadastral system. An approach is proposed according to which a geospatial database is formed, which contains a set of information about all objects of the nature reserve fund and other nature conservation purposes within the territory of the Kyiv region and the results of completed land management projects on the organization and establishment of their boundaries. It is established that the formed verified geospatial data of the objects of the nature reserve fund open the possibility to improve the quality of management processes and gradual transition to decision-making based on analytical information.
Keywords: natural reserve fund; geographic information systems; geospatial data; land management; land protection.